Twelve tips to facilitate Interprofessional Education and Collaborative Practice with students on placements in healthcare settings - Martin, Priya; Sy, Michael (The Journal of Practice Teaching and Learning, 2021)
It is acknowledged that the adverse effects of the COVID-19 pandemic will be long-lasting on healthcare organisations. Consequently, healthcare teams will need to work more collaboratively, supporting each other better in the post-pandemic period. Pre-registration clinical placements in healthcare settings provide an ideal opportunity to instil Interprofessional Education and Collaborative Practice (IPECP) skills, values, and competencies in students early-on. It is a common belief that teams need to have students from two or more professions to facilitate IPECP. Whilst this may be the ideal scenario, healthcare settings were struggling even prior to the pandemic to orchestrate such placement opportunities given the complicated logistics and their resource-intensive nature. This 12 tips paper provides clinical educators with practical tips to facilitate IPECP across the whole continuum from a single student on placement, to several students from two or more professions on placement at the same time. These tips, by promoting IPECP in all student placements, have the potential to re-energise IPECP in healthcare settings, thereby contributing to better outcomes for healthcare professionals, organisations, and service users.